Exploring the Nexus Between Cryptocurrency and Islamic Stocks in Indonesia - Cahyani, Nadya Noer; Bayu Arie Fianto (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
This study aims to determine a correlation between cryptocurrency and the ISSI Index. This research uses a quantitative approach with secondary data sources and type of time series data. The data used is the daily return data of the ISSI Index and cryptocurrency in the period January 02, 2018 to December 30, 2022 obtained through TICMI and Bloomberg. The analysis technique in this study uses CCC-MGARCH and DCC-MGARCH which are processed using Oxmetrics Version 7.0 software. The results showed that cryptocurrency correlates with the ISSI Index but the strength of the correlation is still very low, which is below 10%. This research has implications for portfolio managers and investors in managing their portfolio assets to be well diversified. In addition, this research adds to empirical research in the field of capital markets, especially Islamic capital markets related to financial market integration.